2019
DOI: 10.3389/fmicb.2018.03182
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic Prediction: Linking in vitro Virulence to the Genomics of 59 Salmonella enterica Strains

Abstract: The increased availability of whole-genome-sequencing techniques generates a wealth of DNA data on numerous organisms, including foodborne pathogens such as Salmonella. However, how these data can be used to improve microbial risk assessment and understanding of Salmonella epidemiology remains a challenge. The aim of this study was to assess variability in in vitro virulence and genetic characteristics between and within different serovars. The phenotypic behavior of 59 strains of 32 different Salmonella enter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 37 publications
1
28
1
Order By: Relevance
“…A recent study attempted to determine the pathogenicity potential of various isolates of Salmonella in humans by comparing whole genome sequencing and the presence of known virulence genes to a phenotypic assessment of in vitro virulence (60). Within that study, S. 4, [5],12:i:-was considered to have a high probability of in vitro infection [P (inf)], similar to but slightly less than that of S. Typhimurium, which had the highest probability of all isolates studied.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study attempted to determine the pathogenicity potential of various isolates of Salmonella in humans by comparing whole genome sequencing and the presence of known virulence genes to a phenotypic assessment of in vitro virulence (60). Within that study, S. 4, [5],12:i:-was considered to have a high probability of in vitro infection [P (inf)], similar to but slightly less than that of S. Typhimurium, which had the highest probability of all isolates studied.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, only one of the S. Typhimurium isolates (ISU-SAL243-14) displayed these genes. The sodC1 gene, however, was present in the S. Typhimurium and S. 4, [5],12:i:-strains tested but absent in S. Derby; this gene was associated with high P (inf) and has been previously described to be present in S. 4, [5],12:i:-and S. Typhimurium (60). That study focused on the genetic determinates of disease in humans and it is unclear how transferrable these results are to swine, therefore, further work is needed to better understand the genetic determinates of virulence within the swine host.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, plasmid genes (spvABCDR, pefABCD, rck and mig-5) were detected in the present work in equal numbers and its location was confirmed in the plasmid pSLT, being that the S. Typhimurium strains isolated from humans and food studied had all the plasmid genes mentioned previously or none (Tables 3 and 4). According to Kuijpers and collaborators (2019), the spvABCDR, pefABCD, rck and mig-5 plasmids genes were detected only in the human cases associated with serovars Typhimurium and Enteritidis [38].…”
Section: Plos Onementioning
confidence: 99%
“…Traditional serotyping may be replaced by more robust in silico platforms such as SeqSero, which allows the integration of the Salmonella classical serotyping scheme into a whole-genome sequencing (WGS)-based serotyping inference [ 66 ]. Recent genomics-based studies reveal that the attribution of phenotypical characteristics to individual Salmonella strains or serovars is not enough to improve the hazard characterization [ 67 ]. Studies have shown that the genomics data (without serotyping) of Salmonella isolates can efficiently be used in epidemiological and prevalence-related risk assessments [ 65 , 68 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that the genomics data (without serotyping) of Salmonella isolates can efficiently be used in epidemiological and prevalence-related risk assessments [ 65 , 68 ]. Moreover, a recent paper reports that the variation in the phenotypical characteristics (such as in vitro virulence) among individual strains from the same serovar is more significant than that found between serovars [ 67 ]. Therefore, the lack of serotype information in our study does not confound our findings of the relationship between phenotypic AR and virulence genes.…”
Section: Discussionmentioning
confidence: 99%